Island food systems and unhealthy food imports - Brewer, Tom; Eriksson, Hampus; Ravuvu, Amerita; Roscher, Matthew (WorldFish, 2024)
Unhealthy food imports are a major driver of island food system outcomes in the Pacific. To quantify the challenge of addressing this driver, we present a series of trends of imports of unhealthy foods by Pacific Island Countries and Territories (PICTs) across a set of standard unhealthy food groups (Swinburn, et al. 2013), as well as by exporting region.